Carte geÌneÌrale du Canada, de la Louisiane, de la Floride, de la Caroline, de la Virginie, de la Nouvelle Angleterre, etc. - Anville, Jean Baptiste Bourguignon d', 1697-1782 (P. Santini, Chez Mr. Remondini, 1776)
Map shows settlements, colonies, areas of Native American habitation, and physical features along the eastern coast of North America from Canada and the Gulf of the St. Lawrence to upper Florida and as far west as the Mississippi River and French "Louisiane" territory. Includes notes. Inset: [Map of the waterways in the upper northeastern portion of North America]. Relief shown pictorially. Scale [ca. 1:6,000,000] and Scale [ca. 11,000,000].